PENGARUH KOMPLEKSITAS AUDIT, LOCUS OF CONTROL DAN RESIKO KESALAHAN TERHADAP KUALITAS AUDIT - Ni Luh Tina Gayatri; Ni Wayan Yuniasih (UNHI Press, 2021)
This study had purpose to determine the effect of task complexity structure, locus of control and risk of error on audit quality at KAP in Bali Province. This study uses 80 respondents who are used as samples. In this study, the sampling used purposive sampling technique with certain considerations. The data analysis technique used is multiple linear regression analysis. Based on the analysis, it is found that audit complexity has a negative effect on audit quality at KAP in Bali Province. This shows that the increasing complexity of audits at KAP in Bali Province will tend to reduce audit quality. Locus of control has a positive effect on audit quality at KAP in Bali Province. This shows that the increasing loc in KAP in Bali Province will tend to increase audit quality. The risk of error has a negative effect on the audit quality. This shows that the increased risk of error in KAP in Bali Province, it tends to reduce the quality of the audit